Susceptible Surface Sulfide Regulates Catalytic Activity of CdSe Quantum Dots for Hydrogen Photogeneration - Fan, Xiang‐Bing; Yu, Shan; Wang, Xian; Li, Zhi‐Jun; Zhan, Fei; Li, Jia‐Xin; Gao, Yu‐ji; Xia, An‐Dong; Tao, Ye; Li, Xu‐Bing; Zhang, Li‐Ping; Tung, Chen‐Ho; et al. (Advanced materials (Weinheim), 2019)
Semiconducting quantum dots (QDs) have recently triggered a huge interest in constructing efficient hydrogen production systems. It is well established that a large fraction of surface atoms of QDs need ligands to stabilize and avoid them from aggregating. However, the influence of the surface property of QDs on photocatalysis is rather elusive. Here, the surface regulation of CdSe QDs is investigated by surface sulfide ions (S2−) for photocatalytic hydrogen evolution. Structural and spectroscopic study shows that with gradual addition of S2−, S2− first grows into the lattice and later works as ligands on the surface of CdSe QDs. In‐depth transient spectroscopy reveals that the initial lattice S2− accelerates electron transfer from QDs to cocatalyst, and the following ligand S2− mainly facilitates hole transfer from QDs to the sacrificial agent. As a result, a turnover frequency (TOF) of 7950 h−1 can be achieved by the S2− modified CdSe QDs, fourfold higher than that of original mercaptopropionic acid (MPA) capped CdSe QDs. Clearly, the simple surface S2− modification of QDs greatly increases the photocatalytic efficiency, which provides subtle methods to design new QD material for advanced photocatalysis. To unravel how surface sulfide ions (S2−)regulate photocatalytic hydrogen evolution of CdSe quantum dots (QDs), the different roles of introduced S2− on QDs are revealed. The results show that S2− at an earlier stage grows into the lattice and accelerates electron transfer, while afterward the S2− works as ligands and promotes hole transfer, and thus greatly improves the photocatalytic hydrogen evolution efficiency.